2012
DOI: 10.4103/0253-7176.108229
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-induced Remission of Gardner Diamond Syndrome

Abstract: We describe the clinical presentation of a 25-year-old female patient who presented in dermatology with recurrent episodes of painful ecchymotic bruising over the anterior aspect of both arms and face. On enquiry, these episodes were precipitated by emotional stress and were preceded with a history of fall from the stairs. The patient also had multiple stressors in her day-to-day life and symptoms of depression. A diagnosis of mild depressive disorder without somatic complaints and Gardner Diamond syndrome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…In these cases, a decrease in psychiatric symptoms, a resolution of recurrent bruising and pain symptoms, and a decrease in recurrence of the disease was observed after treatment, with patients reporting feeling better. 5,[10][11][12] Consistent with these previous reports, we also observed that symptoms decreased and resolved following initiation of SSRI therapy.…”
Section: Discussionsupporting
confidence: 90%
“…In these cases, a decrease in psychiatric symptoms, a resolution of recurrent bruising and pain symptoms, and a decrease in recurrence of the disease was observed after treatment, with patients reporting feeling better. 5,[10][11][12] Consistent with these previous reports, we also observed that symptoms decreased and resolved following initiation of SSRI therapy.…”
Section: Discussionsupporting
confidence: 90%
“…The patients reported commonly disclose hysterical and psycho-infantile personality traits, emotional vulnerability, tendency to somatic reactions to emotional stimuli, sexual complains, feelings of hostility, dysphoric-explosive behaviour and obsessive-compulsive disorder. [ 5 6 7 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, psychotropic medications were successfully prescribed according to type of psychopathological disorders and psychotherapy was used to improved skin condition and psychic disorders. [ 6 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation